A new opportunity of restoration and modernization of the old Sobieski’s Palace located at Bernardyńska 13 in Lublin - Wrana, Jan; Jarocka, Aleksandra (Budownictwo i Architektura / Civil and Architectural Engineering, 2012)
The article concerns a question of revitalising the “Sobiescy” Palace Complex in Lublin as well as various possibilities of revalorising it. The authors demonstrate problems of and defects in the technical condition of the building while referring to expert opinions on specific elements of the facilities in question. In order to exemplify chances resulting from prospective modernisation of the discussed complex the authors present already revitalised buildings in Poland. With the purpose of showing considerable potential of the edifice the authors set forth a developed, but unfortunately not implemented project of revitalising the Palace Complex. Moreover, the authors illustrate a new idea for revitalising the facilities in question. The last paragraphs of the article present an outline of creating a Regional Centre of Identity and Cultural Dialogue that would be a chance for popularizing architecture and developing not only Lublin Region but also creativity of its citizens. Moreover, adapting the complex would also provide opportunities for recalling multiculturalism of the region and identity resulting from this feature.